Determination of 38 pharmaceuticals and personal care products in water by lyophilization combined with liquid chromatography-tandem mass spectrometry. Issue 3 (5th January 2021) - Zhang, Yiqing; Lin, Lifeng; Li, Yan; Zeng, Qiaoting; Guo, Shanshan; Nkinahamira, François; Yu, Chang-Ping; Sun, Qian
Abstract : A low-cost and convenient method for 38 PPCP detections in water samples was developed by lyophilization combined with LC-MS/MS. Abstract : A convenient, effective, and low-cost method was developed for the determination of 38 pharmaceuticals and personal care products (PPCPs), including 19 antibiotics in surface water samples by lyophilization combined with liquid chromatography-tandem quadrupole mass spectrometry (LC-MS/MS). The components of the extraction solvent, the volume of the water sample, and the volume of extraction solvent were successively optimized. The analytes in 80 mL water samples were concentrated by lyophilization, eluted effectively by the solvent of 2 mL acetonitrile, 2 mL acetone, and 2 mL ultrapure water. The method detection limits ranged from 0.02 ng L −1 (caffeine) to 0.17 μg L −1 (glibenclamide). The recoveries of 30 analytes ranged from 40.0% (sulfaguanidine) to 124.4% (flumequine). The relative standard deviations of all analytes were below 21% except ciprofloxacin (29%). The performance of the optimized method was comparable to the solid phase extraction and ultrasonic extraction method with much less consumption of labor, organic solvent, and consumables. The developed method was successfully applied to surface river water, reservoir water, and effluent of the wastewater treatment plant.